Depressive symptoms in clinical and incipient Alzheimer's disease. (April 2013) - Hsiao, Julia J; Teng, Edmond
SUMMARY The updated diagnostic criteria for Alzheimer's disease (AD) distinguish three stages: dementia, symptomatic predementia (i.e., mild cognitive impairment) and asymptomatic predementia. Although AD is primarily associated with cognitive deficits, comorbid depressive symptoms frequently occur at each stage. Depression in AD dementia is qualitatively different from depression in cognitively intact and/or younger populations, and may be less responsive to established interventions. In mild cognitive impairment, depressive symptoms are associated with higher rates of progression to dementia, and may identify a subset of individuals that are more responsive to acetylcholinesterase inhibitor treatment. Clinical and subsyndromal depressive symptoms in cognitively normal elderly individuals represent a risk factor and/or prodrome for dementia due to AD; however, sustained antidepressant therapy may be able to modulate this risk.